Corporate Etiquette and Culture of Communication (Laisvalaikio tyrimai, 2021)
Object of the analysis. Investigation problem. This article’s aim is to reveal the features of corporate etiquette and communication culture. The article deals with such topics as: communicative culture, indicators of speech culture in business communication, types, forms and styles of corporate communication. Particular attention is paid to the skills that a person needs to have in order to communicate in business sphere. The article is devoted to the current problem of corporate etiquette and communication culture, since in any situation it is necessary to have a good vocabulary, competently delivered speech, the ability to correctly exit a difficult conversation and have all the necessary skills for work and business communication.Research methods. Scientific literature analysis, synthesis, generalization. Analysis of scientific literature. In this article, when analyzing the texts of different authors, certain components are used, such as communicative culture, etiquette, communication, self-identity, will be separated from the whole and analyzed to justify the goal.Systematic data analysis is performed. Methodological direction of research, which is based on the analysis of interconnections and connections of a complex integral object with many elements, their totality. In this article, some of the components, such as communication culture, etiquette, communication, self, will be analyzed as part of a whole. Outcomes and conclusions. Based on the above, it can be concluded that corporate etiquette and communication culture play an important role in professional spheres and business relationships. With the help of in-depth study and formation of these qualities, and their implementation in all areas of study, such as: tourism, restaurant business and hotel business, management, and everything related to communication and interaction of people, this will give an opportunity in professional activities to prove oneself as educated, communicative and professional personality. Thanks to the ability to use these skills, you can bypass various conflict situations and get out of them professionally, in this regard, professionalism and confidence will grow along with experience in any areas.Keywords: communicative culture, etiquette, communication, own personality